DETERMINAN AKTIVITAS SELF-CARE PADA PASIEN DM TIPE 2 DI RSUD LABUANG BAJI - Natalia Paskawati Adimuntja (Journal Health & Science : Gorontalo Journal Health and Science Community, 2020)
Epidemiological transitions are characterized by increasing non-communicable diseases in the community. One of the non-communicable diseases that are found is Diabetes Mellitus (DM) type 2 disease. The purpose of this research is to know the determinant of self-care diabetes activity in patients with type 2 diabetes at the Labuang Baji Hospital in Makassar City. The research design is cross-sectional study. The population is all patients with type 2 diabetes DM treatment in 2016. Sampling is done by probability sampling technique with simple random sampling method and the number of sample 136 people. The results showed that respondents with self-care activities were less than 35 people (25.7%) and respondents with good self-care activities as many as 101 people (74.3%). The result of bivariate analysis (chi-square) showed that significant factor was correlated with self-care activity of DM type 2 patients with p-value